2013
DOI: 10.1177/0018726713486820
|View full text |Cite
|
Sign up to set email alerts
|

Family ties: Migrant female business owners doing identity work on the public–private divide

Abstract: This article contributes to the literature on identity work and small business studies, by identifying various forms of identity work of female business owners of Turkish and Moroccan descent in the Netherlands, in relation to two sets of identity regulations stemming from their families, regarding the norms of ‘being a good woman’ and ‘dealing with family support’. Identity work refers to the way subjects form, maintain, strengthen or revise constructions of self in relation to the claims and demands issued o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(98 citation statements)
references
References 53 publications
5
90
1
2
Order By: Relevance
“…Culturally specific norms that constrained entrepreneurship were also found: for example, norms of family/ kinship restrained married female entrepreneurs from building relationships with men who were not their husbands. The constraining influences of norms of religion and family/kinship and ethnicity have been observed in other developing countries such as India (Munshi and Rosenzweig, 2006), Turkey and Morocco (Essers et al, 2013). Culturally specific norms of offering and receiving credit and 'African punctuality' confirmed that entrepreneurs need to understand the basis for building networks and trust relationships in distant markets, as these may vary across different cultural contexts (Hall, 1983;Dietz et al, 2010;Adams and Van Eerde, 2010).…”
Section: Norms In Intercontinental Marketsmentioning
confidence: 95%
See 2 more Smart Citations
“…Culturally specific norms that constrained entrepreneurship were also found: for example, norms of family/ kinship restrained married female entrepreneurs from building relationships with men who were not their husbands. The constraining influences of norms of religion and family/kinship and ethnicity have been observed in other developing countries such as India (Munshi and Rosenzweig, 2006), Turkey and Morocco (Essers et al, 2013). Culturally specific norms of offering and receiving credit and 'African punctuality' confirmed that entrepreneurs need to understand the basis for building networks and trust relationships in distant markets, as these may vary across different cultural contexts (Hall, 1983;Dietz et al, 2010;Adams and Van Eerde, 2010).…”
Section: Norms In Intercontinental Marketsmentioning
confidence: 95%
“…Norms underpinning ties embedded in contracts (Macneil, 1980;Sobel, 2008), family and kinship (Granovetter, 1985;Drakopoulou-Dodd, 2011), religion (Dana, 2010;Drakopoulou Dodd and Gotsis, 2007), trade associations (Lyon and Porter, 2009), credit relations (Amoako and Lyon, 2014) have been driving entrepreneurial relationships in various contexts. However, it is possible that, for example, norms of gender and religion (Munshi and Rosenzweig;Essers et al, 2013) as well as loyalty and strong reciprocity within certain networks (Lyon and Porter, 2009) could constrain enterprise development.…”
Section: Normsmentioning
confidence: 99%
See 1 more Smart Citation
“…As hierarchy is a salient feature of Indian society explained by high power distance (Singh, zhao, and Hu 2005), it plays an important part in family structure and functionality in which seniors, particularly male figures, are given paramount authority (Budhwar, Saini, and Bhatnagar 2005). Women in such patriarchal societies are nurtured in childhood and adolescence to serve the male (Basham 2005;Essers, Doorewaard, and Benschop 2013). these values prescribing the roles and responsibilities of women are so deeply ingrained in South Asian societies that women are likely to maintain their home country's cultural roles when they settle in host countries.…”
Section: Mixed Embeddedness Theory Explaining the Entrepreneurship Ofmentioning
confidence: 99%
“…As the topic matures, scholars have stressed the need for new research directions 'to capture more and richer aspects of women's entrepreneurship' (Ahl 2006, 610;Calas, Smircich, and Bourne 2009;Hughes et al 2012;Gutiérrez, Fuentes, and Ariza 2014). For instance, authors have stressed the need for a collective focus on women entrepreneurs to enable an understanding of contextual and cultural variables rather than an individualist focus (Essers, Doorewaard, and Benschop 2013). Research further points to the need for explorative qualitative rather than analytic quantitative techniques for a more robust understanding of the phenomenon of women's entrepreneurship to 'shed light on the actions and efforts in entrepreneurship unique to women' (Ahl 2006;Brush and Cooper 2012, 5;Hughes et al 2012).…”
Section: Introductionmentioning
confidence: 99%